Framing refugees: how the admission of refugees is debated in six countries across the world - Drewski, Daniel (Contestations of the liberal script-scripts, 2024)
This title explores the responses to admitting refugees adopted by governments in six different countries. It shows that government policy - as well as the stance of opposition parties - is dependent on the framing of both the country's collective identity and the identity and characteristics of the refugees.